The Role of Human Resource Management in Improving Employee Performance at the Department of Fire and Rescue Services - Syadida, Muh. Khaulan; Katjina, Husna; Rusdin (Institute for Research and Community Service, 2024)
This study examines the role of Human Resource Management (HRM) in improving employee performance at the Fire and Safety Department of Buton Regency. The background of this research lies in the importance of managing human resources effectively to ensure optimal performance in high-risk public service sectors such as firefighting. The study aims to identify how HRM functions—specifically organizing, preparation, employee development, compensation, and discipline—contribute to enhancing employee effectiveness and organizational productivity. The research employs a qualitative descriptive method, using observation, interviews, and documentation techniques to collect data from key informants, including department officials and employees. The results reveal that the Fire and Safety Department has implemented HRM strategies effectively through structured workforce planning, continuous training, employee development programs, performance-based compensation, and strict disciplinary systems. These practices have significantly improved employee readiness, motivation, and overall performance in handling emergency situations. The study concludes that strong HRM implementation plays a crucial role in building a competent, disciplined, and responsive workforce capable of achieving organizational goals and ensuring high-quality public service delivery.